The Effects of Differences in Post Canal Widths on Microleakage in Prefabricated Fiber Reinforced Composites - Ni Kadek Sugianitri (SONDE (Sound of Dentistry), 2020)
Introduction: Fiber Reinforced Composite (FRC) post is one of the choices in post root canal treatment. Resin cement polymerization results in shrinkage, creating micro gaps between the FRC posts and the root canal wall. This study aimed to find microleakage differences of prefabricated FRC posts with different root canal diameters. Methods: Twenty four maxillary central incisors were used, the root length was 13 mm from the apex. The root canal was prepared with conventional technique and then filled with a single cone technique. Samples were divided into 4 treatment groups of 1.2 mm, 1.4 mm, 1.6 mm and 1.8 mm diameter, cemented, then coated with sticky wax and nail polish and immersed in 2% methylene blue liquid and put into an incubator at 37o for 72 hours. Objects were divided into two mesiodistal directions, observed under a 20x-magnification stereomicroscope. Results: Kruskal-Wallis test showed significant differences in all treatment groups (p <0.05). Mann-Whitney test showed differences between groups (p<0.05) of Ø 1.2 mm and Ø 1.6 mm, Ø 1.2 mm and Ø 1.8 mm, and Ø 1.4 mm and Ø 1.8 mm group. Discussion: The main cause of microleakage at the edge of restoration is because the resin cannot completely close the edges, resulting in shrinkage and contraction during polymerization of the composite resin. Conclusion: There were microleakage in the four groups, the wider root canal might lead to greater microleakage. Keyword?Microleakage, FRC, root canal diameters.